Agroclimatic zoning for Lesquerella fendleri, a multipurpose oilseed crop for production in Argentina - Falasca, Silvia Liliana (2018)
Lesquerella produces a small seed that has 25 to 30% oil, containing 55 to 64% hydroxy fatty acid. The oil is useful for industrial applications, cosmetics, pharmaceuticals and biodiesel. Lesquerella is valued for both its oil and gum. The gum can be used as a thickener in various industrial and food products. The aim of this paper was to develop an agro-climatic zoning model to determine the potential growing areas for Lesquerella fendleri in Argentina. To define the agroclimatic suitability of this crop, the climatic data of the meteorological stations corresponding to the period 1981-2010 were analyzed. The moisture factor, in particular the average annual isohyets of 250, 400 and 1100 mm, was first examined. Annual rainfalls lower than 250 mm determined a non-suitable area, from 250-400 mm the area was deemed suitable, optimal from 400–1100 mm and >1100 mm included another suitable area. The thermal factor was also considered, and annual temperatures < 13ºC determined a non-suitable area. For the growing period, different ranges of temperatures were contemplated: temperatures below 8ºC defined a non-suitable area; from 8 to 11ºC a suitable one; while between 11 and 18ºC the area was optimal and temperatures greater than 18ºC defined another suitable area. Finally, it was determined that the intensity of the winter frosts should be less than -10ºC, so as not to have a lethal impact on Lesquerella. Based on international bibliography, the authors outlined an agro-climatic zoning model for L. fendleri, where 7 classes of suitability were differentiated. This work was performed by the implementation of a Geographic Information System. The GIS database can be updated easily in the future with new data or with better spatial resolution data. If the purpose of the crop is to obtain pharmaceutical compounds, cultivation in optimal, very suitable, suitable and suitable with irrigation would be recommendable. Instead, if the oil is to be destined for biodiesel production, it is convenient to relocate cultivation to areas classified as suitable under subhumid and semiarid regime. Growing this cash crop in semi-desert regions would ensure lack of competition with lands destined for traditional crops.